The Local Heroes Project: a youth-led pan-India hyperlocal crisis relief model during the COVID-19 pandemic - Patil, Dhrumil; Shah, Priyansh; Rao, Shirish; Arora, Anoushka; Shah, Devarsh; Sarangi, Pratik; Gogoi, Krittika; Dutta, Manaswi; Thakore, Yashsri; Pawar, Srushti; Zhang, Zhenyu; Swaroop, Mamta (Frontiers in Public Health, 2023)
Introduction There was shortage of essential diagnostic and therapeutic supplies in public hospitals during the second wave of COVID-19 in India. Materials and methods The Local Heroes Project, a hyperlocal project initiated by the World Youth Heart Federation (WYHF). Pilot project was conducted in six cities, and a nationwide project was scaled up to 58 city groups with 438 volunteers. Three-step model of needs assessment, fundraising, and establishment of the supply chain was undertaken. A national team was formed consisting of representatives from multiple international organizations and stakeholders. Local Volunteers were recruited and empowered in each city to conduct donation drives. The Qualitative Comparative Analysis (QCA) model was used to assess the impact of the intervention. Results 48.2% of the city groups completed needs assessment and 37.9% completed their donations. Factors such as team strength more than 4, local needs assessment, regular reporting during monthly meeting, receptive local administration, donation to more than 2 health centers and donation of supplies worth >= Rs 5,000 in each city (raw coverage 0.44, consistency 1) were more important contributors for success of the outcome. Supplies worth INR 2.45 million were donated. Conclusion Hyperlocal projects can effectively address essential supply shortages. A three-step model of needs assessment, fundraising, and supply chain establishment can be an effective approach. Community involvement and donations are crucial for the success and sustainability of such projects.